Cristo na era digital: interface da comunicação digital com a cristologia de J. Moltmann - Deffaveri, Maiko (2011)
This dissertation examines the impact of the Internet in the conception of the person of Jesus Christ among Catholic youth of Rio Grande do Sul, constructing a dialogue with the thought of the Theologian Jürgen Moltmann. To this end, it presents a qualitative study with focus groups interviews with young Catholics in four cities of Rio Grande do Sul. Initially, the article traces the christological itinerary of Moltmann, highlighting their his theology from the dimension of hope, emphasizing the Christopractice. It then it presents the characteristics of the digital age as well as the characteristics of the present generation youth. It also presents the epistemological assumptions that guide the work. The methodological procedures are the following: focus group as a technique; the audience researched; the inerpretation follows de lines of the methodological framework of depth hermeneutics, that serves as a broad framework in the analysis of symbolic forms of communication. The data are systematized and categorized, and are interpreted according to the pressuppositions of the Christology in messianic dimensions of J. Moltmann, trying to answer the question: who is Jesus Christ for us today?